Swedish family policy – facts and prospects - Michailakis, Dimitris (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2019)
Sweden has since 1970’s step-by-step developed several foundational welfare policies that have helped to encourage equality. Family policy is based on the dual-earner family and asserts the same rights and obligations regarding family and labour market work for both partners.Sweden was the first country to introduce paid parental leave also to fathers in 1974. Swedish family policies encourage both parents to work and share the upbringing of children. Parents receive a generous parental leave package, have flexible employment choices, and a relatively low gender wage gap, while children have high quality childcare, and other services, and a substantial child benefit programme. A brief review of the Swedish welfare state is discussed parallel with critical appraisals of family policies